Transfer of the Posterior Tibial Tendon for Chronic Peroneal Nerve Palsy. Issue 7 (July 2021) - Wakefield, Connor J.; Hamid, Kamran S.; Lee, Simon; Lin, Johnny; Holmes, George B.; Bohl, Daniel D.
Abstract : The common peroneal nerve (CPN) is one of the most frequently injured nerves of the lower extremity. One-third of patients who develop CPN palsy proceed to chronic impairment without signs of recovery. Ankle-foot orthoses can provide improvement with respect to gait dysfunction and are useful as a nonsurgical treatment option. Severe cases of CPN palsy demonstrating no signs of recovery may require operative intervention with tendon transfer.